A preliminary study of stakeholders’ opinions and perceptions of elephants and elephant management in Botswana - Adams, Tempe; Chase, Michael; Attard, Anna; Leggett, Keith (Pachyderm, 2020)
Botswana has been lauded by the international conservation community for maintaining the largest population of African elephants on the continent. However, given the size of the elephant population and increasing human population in Botswana, elephants and people are forced at times to live in close proximity to each other, making human–elephant conflict difficult to avoid. It is widely acknowledged that the management of protected areas and wildlife is often a complicated and contentious issue, which requires participation by all stakeholders. This preliminary study aims to determine stakeholders’ opinions and perceptions of elephants and elephant management in Botswana. Questionnaires were distributed nationwide and were completed on a voluntary basis. The majority of those who responded, valued elephants for intrinsic reasons, such as their being part of the environment; however, there were concerns over the lack of management and how best to manage the population in the future. These concerns stemmed in part from the perceived lack of communication among stakeholders. There was a significant difference in opinion between those that lived inside and outside of the elephant range. The study provides an insight into stakeholders’ opinions and perceptions of elephant management in Botswana, providing inputs for an improved management strategy, aimed at reducing the incidence and impact of human–elephant conflict in Botswana. La communauté internationale de la conservation a loué le Botswana pour le maintien de la plus grande population d’éléphants d’Afrique sur le continent. Cependant, compte tenu de la taille de la population d’éléphants et de la démographie croissante au Botswana, les éléphants et les populations humaines sont obligés parfois de vivre à proximité les uns des autres, ce qui rend le conflit entre les hommes et les éléphants difficile à éviter. Il est largement reconnu que la gestion des aires protégées et de la faune est souvent une question compliquée et contestée qui nécessite la particpation de toutes les parties prenantes. Cette étude préliminaire vise à déterminer les opinions et les perceptions des parties prenantes concernant les éléphants et leur gestion au Botswana. Des questionnaires ont été distribués dans tout le pays et remplis sur une base volontaire. La majorité de ceux qui ont répondu apprécient les éléphants pour des raisons intrinsèques comme faisant partie de l’environnement tout en exprimant des soucis quant au manque de gestion et à la meilleure façon de gérer la population à l’avenir. Ces préoccupations découlent en partie du manque de communication entre les parties prenantes. Il y avait une différence significative d’opinion entre ceux qui vivaient à l’intérieur et à l’extérieur de l’habitat des éléphants. L’étude donne un aperçu des opinions des parties prenantes et des perceptions au sujet de la gestion des éléphants au Botswana, ce qui contribuerait à une stratégie de gestion améliorée, visant à réduire l’incidence et l’impact du conflit homme-éléphant au Botswana.